Use Patterns and Costs of Isolated Limb Perfusion and Infusion in the Treatment of Regional Metastatic Melanoma: A Retrospective Database Analysis. Issue 2 (February 2016) - Ma, Qiufei; Zhao, Zhongyun; Barber, Beth; Shilkrut, Mark
Abstract Introduction Isolated limb perfusion and infusion (ILP/ILI) are therapies for regional metastatic melanoma that allow high doses of anticancer drugs to be delivered directly into the circulation of an affected limb, thereby minimizing systemic drug toxicity. This procedure can lead to high response rates and is recommended in patients with Stage III unresectable metastatic melanoma. However, limited information is available on patterns of use and costs. This study examined patterns of ILP/ILI use and associated costs in patients with melanoma in the United States (US). Methods Retrospective, observational study, using administrative claims data from the MarketScan® databases, was performed in patients with a diagnosis of melanoma (ICD-9-CM: 172.xx, V10.82) who underwent ILP/ILI (CPT-4: 36823) between January 1, 2002 and March 31, 2013. Patient characteristics, use patterns, length of hospital stay, and costs (per 2014 US ) of ILP/ILI were assessed. Results One hundred and thirteen patients met the study criteria and were included in the analysis. Mean age was 61.4 years (standard deviation [SD] 13.8) and 38.9% of patients were male; the mean baseline Charlson Comorbidity Index was 0.19; 34.5% of patients were Medicare beneficiaries. The majority of patients (87.6%) had melanoma of the lower limb, 11.5% of the upper limb, and 0.9% of both limbs; 60.2% had lymph node metastasis and 56.6% had skin metastasis. Four patients (3.5%) underwent multiple ILP/ILI. The mean (±SD) length of hospital stay was 5.6 (±3.5) days and the mean (±SD) cost was US36, 758 (±27, 124) per ILP/ILI procedure. Conclusions Isolated limb perfusion and infusion in patients with melanoma were associated with long hospital stays and high costs. These results provide useful source data for the economic evaluation of treatment options for regional metastatic melanoma. Funding This study was funded by Amgen, Inc.